Do transparency and accountability enhance regulatory compliance in public procurement? Evidence from Tanzania - Goodluck G. Ntangeki; Ismail A. Changalima; Scholastica N. Justus; Denis C. Kawishe (African Business Management Journal)
With an increasing emphasis on ethical practices among public procurement practitioners, transparency and accountability will remain critical in ensuring effective and efficient procurement operations. This paper examines the influence of transparency and accountability in enhancing regulatory compliance in public procurement. This study was quantitative in nature and utilised a quantitative analysis approach to analyse data from 202 public procurement practitioners in Dodoma, Tanzania. The study applied structural equation modelling to examine the relationship between transparency, accountability, and regulatory compliance in public procurement. The results indicate a positive and significant relationship between transparency and regulatory compliance (β = 0.148, p = 0.048). The study also reveals that accountability is a significant and positive factor that promotes regulatory compliance (β= 0.366, p < 0.001). The study’s findings offer valuable insights for public procurement practitioners to establish well-defined standards of practice concerning transparency and accountability in procurement operations, with the aim of improving regulatory compliance. The research contributes to the existing literature on enhancing procurement compliance in the public sector by exploring the role of transparency and accountability in procurement regulatory compliance in Tanzania.